Enhancing Student’ Speaking Ability By Using Student’ Centered Learning At Faculty Of Teacher Training And Education Of Tridinanti University Palembang - Gaya Tridinanti (Jurnal Didascein Bahasa, 2015)
Abstract : The problem of this study was to find out whether it is effective or not to use studentsÃ¢â‚¬â„¢ centered learning strategy in enhancing studentsÃ¢â‚¬â„¢ speaking ability. It aims to find out the effectiveness of studentsÃ¢â‚¬â„¢ centered learning method to enhance studentsÃ¢â‚¬â„¢ speaking ability. The population was all of the students of Faculty of Teacher Training and Education of Tridinanti University Palembang inÃ‚Â academic year 2013-2014. They were 32 students and taken by using random sampling. The method was pre-experimental method by using pre-test and the post-test design. The data were obtained by means ofÃ‚Â the test, the results were analyzed through the match t-test calculation. Based on theÃ‚Â finding, the writer found that the average score in the pre-test was 62.97, and the average score in the post-test was 75.62. From the matched t-test calculation, the writer got that t-obtained was 4.85. It showed that t-obtained was higher than critical value (1.684) . It can be concluded that it was effective to use studentsÃ¢â‚¬â„¢ centered learning strategy in enhancing studentÃ¢â‚¬â„¢ speaking ability at Faculty of Teacher TrainingÃ‚Â and Education of Tridinanti University.Keywords : speaking ability, studentsÃ¢â‚¬â„¢ centered learning.